A missed opportunity: United States v Hall and the battle over the Fourteenth Amendment - Clauson, Loryn (Kansas State University, 2015)
During the course of Reconstruction both the Supreme Court and the lower level federal courts faced the task of interpreting Reconstruction legislation, including the Thirteenth, Fourteenth and Fifteenth Amendments and the Enforcement Acts. By the end of Reconstruction the Supreme Court had defined these groundbreaking pieces of legislation in a conservative manner that negatively impacted the former slaves. The lower-level courts, however, had embraced earlier opportunities to broaden the nationalistic meaning of these Amendments. One such opportunity was United States v Hall. This trial level court case initially expanded the scope of the Fourteenth Amendment to protect the rights of African Americans. The Hall Case was one of the great “might have beens” in U.S. Constitutional history. This study analyzes Ku Klux Klan violence leading up to the Eutaw riot and the subsequent court case, U.S. v Hall. Conflict broke out during a pre-election political rally when Democrats and Republicans met simultaneously at the Greene County, AL, Court House. The riot resulted in the federal government’s attempts to prosecute the rioters under the Enforcement Act of 1870. The Hall case was one of the first in which federal judges interpreted the Fourteenth Amendment. Federal prosecutors challenged the judges to make a broad, nationalistic interpretation, which would have enabled the federal government to protect the rights of the former slaves for the long haul. What—exactly—were the privileges and immunities of national citizenship? Did the Fourteenth Amendment apply the Bill of Rights to the states? Are these rights protected against the state governments? These are the issues Attorney General John P. Southworth and Circuit Court Judge William Woods tackled in the federal trial. Ultimately, the government failed to secure a conviction of the rioters but set a strong precedent in Judge Woods’ opinion for later federal courts to establish the Fourteenth Amendment’s connection to the Bill of Rights. Unfortunately, the Supreme Court failed to follow the precedent. This analysis provides historians a better understanding of the work of the lower level federal courts’ and their contribution to the constitutional issues of Reconstruction.
Keywords: United States v Hall; Fourteenth Amendment; Reconstruction; Enforcement Act; Alabama; Circuit Courts; History (0578)